The Mitochondrial Permeability Transition Pore and Cancer: Molecular Mechanisms Involved in Cell Death - Bonora, Massimo; Pinton, Paolo (Frontiers in Oncology, 2014)
Since its discovery in the 1970s, the mitochondrial permeability transition has been proposed to be a strategic regulator of cell death. Intense research efforts have focused on elucidating the molecular components of the mitochondrial permeability transition because this knowledge may help to better understand and treat various pathologies ranging from neurodegenerative and cardiac diseases to cancer. In the case of cancer, several studies have revealed alterations in the activity of the mitochondrial permeability transition pore (mPTP) and have determined its regulatory mechanism; these studies have also suggested that suppression of the activity of the mPTP, rather than its inactivation, commonly occurs in solid neoplasms. This review focuses on the most recent advances in understanding mPTP regulation in cancer and highlights the ability of the mPTP to impede the mechanisms of cell death.